Defenses in contemporary international criminal law - Knoops, Geert-Jan Alexander, 1960- (International and comparative criminal law series., 2008)
The Second Edition of ""Defenses in Contemporary International Criminal Law"" ventures farther into this uneasy territory than any previous work, offering a meticulous analysis of the case law in the post World War II Military Tribunals and the ad hoc tribunals for Rwanda and the Former Yugoslavia, with particular attention to the defenses developed, their rationales, and their origins in various municipal systems. It analyzes the defense provisions in the charters and statutes underlying these tribunals and the new International Criminal Court, while examining the first judgment in this field.